Dampak Techno Overload terhadap Work Performance: Peran Emotional Exhaustion sebagai Variabel Mediasi - Salsabila, Nila; Haqq, Zulkifli Nurul; Firdaus, Firdaus (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The aim of this research is to examine the impact of techno overload on work performance in MSME workers. Apart from that, this research examines the mediating role of emotional exhaustion in workers because of their work. Data was collected from MSMEs that apply technology in Semarang City, Central Java, involving 315 MSME employees as respondents. The approach used is quantitative analysis using the SmartPLS technique. The results show that techno overload influences emotional exhaustion and work performance of MSME employees who use technology, but emotional exhaustion is very weak in mediating between techno overload and work performance. This research provides several theoretical and practical contributions.